Endoscopic ultrasound guided radiofrequency ablation for treatment of pancreatic neuroendocrine tumors: a multicenter prospective study - Rizzatti, Gianenrico; Napoleon, Bertrand; Caillol, Fabrice; Crinó, Stefano Francesco; de Nucci, Germana; Pham, Khanh Do-Cong; Giovannini, Marc; Leblanc, Sarah; della Torre, Silvia; Palazzo, Laurent; Pafundi, Pia Clara; Conti Bellocchi, Maria Cristina; Spada, Cristiano; Larghi, Alberto (Endoscopy International Open)
Background and study aims Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has been proposed as a minimally invasive approach alternative to surgery for treatment of both functional (F-) and non-functional (NF-) pancreatic neuroendocrine tumors (PanNETs). We performed a large prospective multicenter study to evaluate safety and effectiveness of EUS-RFA in patients with F- and NF-PanNETs. Patients and methods Patients with F- (size ≤2cm) and NF-PanNETs (size 15mm-25 mm) were prospectively enrolled over a 43-month period. Primary aim was safety, defined as rate of adverse events (AEs). Secondary aim was effectiveness defined as complete disappearance of the hormonal secretion syndrome in F- PanNETs, while for NF-PanNETs complete response was defined as absence of enhancing tissue and of detectable lesion at MRI/CT scan and Gallium-PET, respectively. The EUSRA 19G needle was used in all patients. After treatment completion, follow-up was performed for 1 year. Results During the study period, a total of 60 patients were enrolled, 30 with insulinomas and 30 with NF-PanNETs (mean lesion size of 14.5±4.5 mm). In 78.3% of patients a single RFA session was performed. Overall, AEs occurred in 9/60 (15%), in four patients (13.3%) with insulinomas and in five (16.7%) with NF-PanNETs, with only one severe AE. Complete insulin hypersecretion symptoms resolution was obtained in 29/30 patients (96.7%) with insulinomas, while for NF-PanNETs complete radiological response was obtained in 22/25 (88%) of patients with a long-term follow up. Conclusions Our prospective international multicenter study demonstrated that EUS-RFA is highly safe and effective for the treatment of both F- and NF-PanNETs.